Cyber Security and Privacy Third Cyber Security and Privacy EU Forum, CSP Forum 2014, Athens, Greece, May 21-22, 2014, Revised Selected Papers - Cleary, Frances; Felici, Massimo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed, selected papers on the Second Cyber Security and Privacy EU Forum, CSP 2014, held in Athens, Greece, in May 2014. The 14 revised full papers presented were carefully reviewed and selected from 90 submissions. The papers are organized in topical sections on security; accountability, data protection and privacy; research and innovation.
Security -- Accountability, data protection and privacy -- Research and innovation.
Keywords: Computer security; Computers and civilization; Application software; Database management; Computer communication systems; Systems and Data Security; Computers and Society; Computer Appl. in Administrative Data Processing; Database Management; Computer Communication Networks